Giant lymph node hyperplasia (Castleman's disease): a clinical study of eight patients. Issue 786 (April 1991) - Baruch, Y.; Ben-Arie, Y.; Kerner, H.; Lorber, M.; Best, L. A.; Gershoni-Baruch, R.
Abstract : We report on 8 patients with giant lymph node hyperplasia (GLNH), diagnosed over a 10-year period. The age of the patients at diagnosis, the clinical presentation and the histological subtype varied, indicating that GNLH is a heterogeneous condition. One case was associated with liver cirrhosis, and in another patient bacterial endocarditis was diagnosed post mortem. Our study shows that GLNH is localized and benign in the young, and diffuse and aggressive in the elderly. It is concluded that GLNH should be separated into 3 clinical entities--namely, localized, systemic and reactive GLNH--defined by their clinical presentation and course, and correlated or not correlated with the histological findings.